The Efficacy of Systemic Therapy for Childhood and Adolescent Externalizing Disorders: A Systematic Review of 47 RCT. Issue 4 (11th September 2013) - von, Kirsten; Retzlaff, Ruediger; Beher, Stefan; Haun, Markus W.; Schweitzer, Jochen
<x xml:space="preserve">Abstract</x> Systemic (family) therapy is a widely used psychotherapy approach. However, most systematic efficacy reviews have focused solely on "family‐based treatment" rather than on the theoretic orientation "systemic therapy." We systematically review trials on the efficacy of systemic therapy for the treatment of childhood and adolescent externalizing disorders. All randomized (or matched) controlled trials (RCT) evaluating systemic/systems‐oriented therapy in various forms (family, individual, group, multi‐family group therapy) with child or adolescent index patients (0–17 years) suffering from mental disorders were identified by data base searches and cross‐references. Inclusion criteria were as follows: index patient diagnosed with a DSM‐ or ICD‐listed mental disorder, and trial published in any language up to the end of 2011. The RCTs were analyzed for their research methodology, interventions applied, and results (postintervention; follow‐up). A total of 47 trials from the United States, Europe, and China, published in English, German, and Mandarin, were identified. A total of 42 of them showed systemic therapy to be efficacious for the treatment of attention deficit hyperactivity disorders, conduct disorders, and substance use disorders. Results were stable across follow‐up periods of up to 14 years. There is a sound evidence base for the efficacy of systemic therapy for children and adolescents (and their families) diagnosed with externalizing disorders.